'Bamboo Hut Technique' to Bridge Large Defects During Tibiotalocalcaneal Fusion. Issue 4 (December 2021) - Shah, Rajiv; Geevarughese, Nikku Mathew; Shah, Shivam
Abstract : Tibiotalocalcaneal arthrodesis is a salvage procedure for severe ankle and hindfoot deformities, cases with bone loss, arthritis, and failed previous surgeries. Complex situations leave the surgeon apprehensive over large bone defects. Several options to bridge the bone gap have been described; however, the easy availability of allografts and cages poses a significant challenge for the less privileged surgeon. Here we describe a simple indigenous technique of utilizing autologous fibula to bridge large bone defects between the tibia and calcaneus during tibiotalocalcaneal fusion. The technique has advantages like the generation of compression at the site of fusion through the indigenously designed nail plus keeping grafts bonded like as in a bamboo hut. Level of Evidence: Diagnostic Level V. See Instructions for Authors for a complete description of levels of evidence.